Botulinum toxin type-A in the treatment of glabellar lines - Leslie Winter; Jeffrey Spiegel (Dove Medical Press, 2009)
Leslie Winter1, Jeffrey Spiegel21Department of Otolaryngology, Boston Medical Center, Boston, MA, USA; 2Chief, Division of Facial Plastic Surgery Boston Medical Center Boston, MA, USAAbstract: The current literature and state of the art on use of botulinum toxin type-A in the treatment of glabellar rhytids was reviewed. Botulinum toxin type-A is a safe and effective way to manage glabellar rhytids. Mastery of the anatomy of the glabellar region, familiarity with the products currently available on the market and judicious dosing results in excellent cosmetic results with minimal adverse events.Keywords: botulinum toxin, glabellar rhytids, cosmetic